Medical countermeasures for national security: A new government role in the pharmaceuticalization of society. (April 2015) - Elbe, Stefan; Roemer-Mahler, Anne; Long, Christopher
Abstract: How do governments contribute to the pharmaceuticalization of society? Whilst the pivotal role of industry is extensively documented, this article shows that governments too are accelerating, intensifying and opening up new trajectories of pharmaceuticalization in society. Governments are becoming more deeply invested in pharmaceuticals because their national security strategies now aspire to defend populations against health-based threats like bioterrorism and pandemics. To counter those threats, governments are acquiring and stockpiling a panoply of 'medical countermeasures' such as antivirals, next-generation vaccines, antibiotics and anti-toxins. More than that, governments are actively incentivizing the development of many new medical countermeasures – principally by marshaling the state's unique powers to introduce exceptional measures in the name of protecting national security. At least five extraordinary policy interventions have been introduced by governments with the aim of stimulating the commercial development of novel medical countermeasures: (1) allocating earmarked public funds, (2) granting comprehensive legal protections to pharmaceutical companies against injury compensation claims, (3) introducing bespoke pathways for regulatory approval, (4) instantiating extraordinary emergency use procedures allowing for the use of unapproved medicines, and (5) designing innovative logistical distribution systems for mass drug administration outside of clinical settings. Those combined efforts, the article argues, are spawning a new, government-led and quite exceptional medical countermeasure regime operating beyond the conventional boundaries of pharmaceutical development and regulation. In the first comprehensive analysis of the pharmaceuticalization dynamics at play in national security policy, this article unearths the detailed array of policy interventions through which governments too are becoming more deeply imbricated in the pharmaceuticalization of society. Highlights: Pharmaceuticals are pivotal to the national security strategies of many countries. States are incentivizing the commercial development of new medical countermeasures. Government-led policies have spawned an exceptional new pharmaceutical regime. Governments are crucial but complex drivers of the pharmaceuticalization of society.